Physical Therapy Management of Adults with Mild Traumatic Brain Injury - Kane, Ashley W.; Diaz, Deborah S.; Moore, Carolyn (Seminars in Speech and Language, 2019)
Rehabilitation for individuals after mild traumatic brain injury (mTBI) or concussion requires emphasis on both cognitive and physical rest, with a gradual return to activity including sports. As the client becomes more active, the rehabilitation professional should pay close attention to symptoms associated with mTBI, such as headache, dizziness, nausea, and difficulty concentrating. The systematic approach to return to play provided by the Berlin Consensus Statement on Concussion in Sport can apply to adults with mTBI. This protocol calls for gradually increasing the intensity of physical activity while attending to postconcussion symptoms. During the incident that led to an mTBI, the injured individual may incur injuries to the vestibular and balance system that are best addressed by professionals with specific training in vestibular rehabilitation, most commonly physical therapists. Benign paroxysmal positional vertigo is a condition in which otoconia particles in the inner ear dislodge into the semicircular canals, resulting in severe vertigo and imbalance. This condition frequently resolves in a few sessions with a vestibular physical therapist. In conditions such as gaze instability, motion sensitivity, impaired postural control, and cervicogenic dizziness, improvement is more gradual and requires longer follow-up with a physical therapist and a home exercise program. In all of the above-stated conditions, it is essential to consider that a patient with protracted symptoms of mTBI or postconcussion syndrome will recover more slowly than others and should be monitored for symptoms throughout the intervention.
Keywords: postconcussion syndrome; postural instability; gaze stability; benign paroxysmal positional vertigo; cervicogenic dizziness; graduated exertion